Diversity and productivity (Chlorophyll-a and Biomass) of periphyton on natural and artificial substrates from wetland ecosystem - Saikia, SK; Das, DN (Journal of Wetlands Ecology, 2011)
Periphyton from rice-fish environment of Apatani Plateau, Arunachal Pradesh, India was studied for diversity and productivity (Chlorophyll-a and biomass) on artificial (glass slide) and natural (rice stem) substrates. Periphyton from rice stems, especially, from cultivars locally known as ‘Amo’ were collected from a depth of 7.0-8.0 cm from surface water and 5.0 cm above from the field bottom. Glass slides (15 × 18cm) were fitted in periphyton sampler and fixed at different depths. The rice fish environment was found to harbor rich periphytic diversity throughout the whole cropping season of 2002 and 2003. Total 88 genera of periphytic microalgae were reported from the environment with an order of preference of Chlorophyceae>Bacillariophyceae>Cyanophyceae. The Shannon Wienner diversity (H´) and evenness (J) indices of periphyton from rice stems indicated tendencies of Chlorophycea and Cyanophyceae to exhibit periphytic life on rice stems, whereas Bacillariophyceae preferred glass slide. Dry matter (DM) and Ash free dry matter (AFDM) values reflected the affinity of non algal periphytic resource to associate on both rice stems and glass slide. The results of periphytic Chl-a from rice stem was significantly higher to glass slides and show selectivity of algal periphytic resource to colonize on rice stem. Its sudden decline during late aquatic phase on rice stem explains heterotrophic nature of rice fish environment. The rice stems as natural substrate, thus, exhibited a rich ground for periphyton growth in rice fields of Apatani Plateau. It also stands as potential candidate to be used as a source for organic nutrients in the form of periphyton for aquaculture. Key words: Apatani plateau; Rice-fish; Common carp; Periphyton; Rice stem DOI: http://dx.doi.org/10.3126/jowe.v5i0.4624 J Wet Eco 2011 (5): 1-9